Furniture Sales Application with Android-Based Qr Code Technology (Case Study "99" Furniture Store) - Muhammad Dzikri Ramadhan; Mohammad Suryawinata (Procedia of Engineering and Life Science, 2021)
The growth of the furniture industry relies heavily on good marketing activities. In this digital and online era can be utilized in terms of marketing in the furniture industry. Toko 99 Mebel is one of the furniture stores that still use conventional transaction and order recording. So product marketing is less innovative and efficient. The purpose of this research was to build an android-based furniture sales application that added a QR Code scan feature that can be a new innovation in 99 furniture stores in marketing products. QR Code serves as a feature to display a description of the product to be ordered quickly. The method used is waterfall, useful to reduce errors in building applications. Testing in this application using the Black Box method, this test method is very important to test the fungisonality of the application as opposed to internal structure or work. With waterfall method and Black Box testing method in application development can be arranged well and appropriately. As well as being able to participate in the sale of 99 Furniture Stores, because it will further facilitate the process of selling furniture online via android smartphone so that it is expected to increase customer interest to buy furniture in 99 Furniture Stores.